Efficient ADE-WE-PML formulations for scalar dispersive FDTD applications - Ramadan, O. (Inst Engineering Technology-Iet, 2013)
Efficient wave equation perfectly matched layer (WE-PML) formulations, based on the auxiliary differential equation (ADE) scheme, are presented for truncating scalar dispersive finite difference time domain (FDTD) grids. The formulations maintain the same accuracy as previous WE-PML approaches but with fewer additional auxiliary variables. Moreover, the formulations can be coupled easily with the classical WE-FDTD scheme.